Organizational Resiliency Framework for Restaurant Establishments - Barlan-Espino, Annie Gay (ASEAN Multidisciplinary Research Journal, 2021)
Organizational resiliency is the capability of an organization to survive an accustomed crisis and grow vigorously in a world that is full of uncertainties. It is a system that identifies the threats coming and moving forward to combat the battle of the crisis. To help the restaurant organization in pandemic times, this study entitled “Organizational Resiliency Framework for Restaurant Establishments” was conducted. This study proposed a resiliency framework for restaurants focusing on the relationship between operational practices and innovation. The firmographic profile of themed restaurants and the profile of the respondents were presented. Also, operational practices of themed restaurants and a series of innovations were determined under the new normal. This descriptive study tested the significant relationship between operation and innovation practices leading to the proposed resiliency framework for restaurants. The findings revealed that participant’s themed restaurant was operating and existed for years, with a limited number of employees and focused on take-out and delivery services offering. The customer respondents are Millennials, mostly female, with enough income per month, spending based on their budget per visit monthly on the themed restaurants. Respondents agreed on operational practices of restaurants, however, disagreed on specific services like having customer self-ordering machines and advising customers to self-swipe cards on payment. Likewise, an agreement was foreseen on innovation practices of restaurants in terms of product, process, management, and marketing innovation by the respondents. Operational practices and innovation have a significant relationship that greatly influences and contribute to the formation of organizations’ resilience in times of pandemics.